Preje in pletiva: Zapiski predavanj - Dobnik Dubrovski, Polona (University of Maribor Press, 2026)
Yarns and Knitted Fabrics: Lecture Notes. Yarns and Knitted Fabrics is a modern teaching material that provides students and professionals in the field of textile engineering design with a basic understanding of the relationship between technology and the structure of finished textile products (yarns and knitted fabrics). The lecture notes systematically cover the classification, structure, and functional properties of yarns and knitted fabrics, as well as conventional and modern spinning (ring, ring compact, siro/solo, open-end, self-twist, wrap, adhesive) and knitting (warp, weft) processes. Special emphasis is placed on evaluating the functional properties of yarns and knitted fabrics, which are key to designing high-quality textile products. The material is partially illustrated, clearly structured, and supported by current sources, which facilitates understanding of the principles of technological processes and the connections between the structure and usability of textiles. It is intended for students of technical fields, textile and clothing designers, researchers, and anyone interested in the development of innovative, sustainable, and technically sophisticated textile products. It is an indispensable source of basic knowledge for anyone who wants to understand established and contemporary trends in the textile industry.